2009
DOI: 10.21608/jva.2009.45137
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Lectin histochemistry of the testes of brown-banded bamboo shark (Chiloscyllium punctatum)

Abstract: Lectin histochemistry of the testes of shark Kassab et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Microscopic observation of M. punctulatus testes revealed a diametric development, in which round-shaped spermatocysts have zonal arrangement. Diametric development, in which spermatogenesis extends from one wall across the diameter of the testis to the opposite wall with efferent ducts [16], was described for the shark families Carcharhinidae, Sphyrnidae, Somniosidae, Centrophoridae, Hemiscylliidae, and Triakidae [17][18][19][20]. The gross testis morphology, association of testis with the epigonal organ, and microscopic anatomy described in this study correspond with the previous studies on closely related sharks [17].…”
Section: Resultssupporting
confidence: 84%
“…Microscopic observation of M. punctulatus testes revealed a diametric development, in which round-shaped spermatocysts have zonal arrangement. Diametric development, in which spermatogenesis extends from one wall across the diameter of the testis to the opposite wall with efferent ducts [16], was described for the shark families Carcharhinidae, Sphyrnidae, Somniosidae, Centrophoridae, Hemiscylliidae, and Triakidae [17][18][19][20]. The gross testis morphology, association of testis with the epigonal organ, and microscopic anatomy described in this study correspond with the previous studies on closely related sharks [17].…”
Section: Resultssupporting
confidence: 84%
“…Diametric testicular development is characteristic of Carcharhinidae and Sphyrnidae testes. In the last 10 years, testes of Triakidae (Rogers, 2013), Somniosidae, Centrophoridae (Girard et al, ) and Hemiscyliidae (Kassab et al, ) shark families have also been recognized to exhibit diametric type of development. In the present study P. glauca and R. lalandii are members of Carcharhinidae family and M. canis is member of Triakidae family.…”
Section: Discussionmentioning
confidence: 99%
“…The present work revealed that the germ cells of the spermatocyte zone expressed all sugars under investigation except fucose (UEA-1), while Kassab et al (2009) reported that the spermatocytes only reacted to the galactose and glucosamine. On the other hand, GlcNAc is prevalent in all the germ cell types in the frog ( Xenopus laevis ) testis and can be identified in the spermatogonial cells (Valbuena et al, 2012).…”
Section: Discussionmentioning
confidence: 46%
“…The current investigation showed that the neutral mucopolysaccharides, identified by the PAS labeling, appeared in the interstitial tissue of the spermatogonial, spermatocyte, and spermatid zones and became more apparent in the spermatozoal–Sertoli cell junction in the spermatozoal zone. These data suggest a role of neutral mucopolysaccharides during the development of shark spermatozoa as well as Sertoli–spermatozoal attachment (Kassab et al, 2009). Also, it was reported that there was a progressive increase in glycosylation during spermatogenesis, especially at the level of the acrosome in the spermatocyte-spermatid step (Liguoro et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation